Pemberian Water Tepid Sponge pada Anak dengan Hipertermia - Inayati Albayani, Melati; Utami, Kusniyati; Aprian, Nurmala (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2022)
During growth and development, children often experience illness, usually followed by several symptoms, including fever. Fever is a state of body temperature above normal as a result of an increase in the temperature regulating center in the hypothalamus. Water tepid sponge is one of the procedures to improve the control of body heat loss through evaporation and conduction, which is performed on patients who have high fever. The method used were a descriptive method with a case study approach and using a nursing approach process in 2 pediatric patients with fever in the Penimbung Health Center Work area. The time of the study was June 2021.All the problems that occurred have been well resolved since the patient was treated with a water edged sponge. The patient has shown significant changes for the better. Giving a tepid sponge is effective in reducing fever in children with fever.